English: English - Rosmawati Abdul Maing; Syahruddin Mahmud (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
ABSTRACT This study explores the teaching practices in junior high schools in Maros Regency, South Sulawesi Province, Indonesia that promote the development of a positive classroom climate. Interviews were used to gather the data. Twenty-four class-teachers from 12 junior high schools participated in individual semi structured interviews. The data collected from teacher interviews were analysed using NVivo version 10. The qualitative analysis revealed that two main teaching practices influenced classroom climate namely student-teacher relationships and behavior management. Five further domains indicative of teaching practices that contributed to a positive classroom climate were positive school-home relationships, teachers’ teaching pedagogies, and positive teachers’ assumptions about student intelligence and capabilities, peer friendships, and behavioral self-control. Eight domains that hindered a positive classroom climate were also presented namely negative school-home relationships, negative, teachers’ assumptions about student intelligence, student mental health, consequences and punishment, negative student interactions with peers, disruptive acts, less attendance and motivation, and students’ difficulties. Keywords: classroom climate, teaching practices, teacher and student relationships